Analisis Nilai Tambah Diversifikasi Produk Turunan Komoditas Kelapa Dalam di Kabupaten Tanjung Jabung Barat - Dianingsih, Yunita; Suandi, Suandi; Ningsih, Rozaina (Universitas Batangahari Jambi, 2025)
The objectives of this study are (1) To describe the picture of diversification of coconut commodity derivative products, (2) To analyze added value and (3) To analyze the differences in added value obtained from diversification of coconut commodity derivative products in West Tanjung Jabung Regency. The data used in this study are primary data and secondary data obtained when the study was conducted. Sampling was carried out by total sampling (census) of 31 farmers. The data analysis method used is a descriptive method using the Hayami method of added value analysis aid table and the statistical test used is One Way Anova with the Statistical Package for the Social Sciences (SPSS) for Windows program with data on coconut commodity derivative product diversification business actors that are not the same. From the calculation, the amount of added value per production process and the profit of coconut commodity derivative products will be known and the difference between the added value obtained from the processing of diversified coconut commodity derivative products will be known. Based on the results of the study, it shows that the ratio of added value of diversified coconut commodity derivative products, namely coconut flesh raw materials (VCO) is 70.37%, coconut flesh raw materials (cooking oil) are 52.33% and coconut sap raw materials (palm sugar) are 59.64% which means that the amount of added value ratio is > 40%, then the added value is classified as high. One Way Anova test of the added value ratio between VCO products and cooking oil products has a significant value of